2012
DOI: 10.1111/1365-2664.12016
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: The role of ecosystems and their management in regulating climate, and soil, water and air quality

Abstract: Summary1. Ecosystems have a critical role in regulating climate, and soil, water and air quality, but management to change an ecosystem process in support of one regulating ecosystem service can either provide co-benefits to other services or can result in trade-offs. 2. We examine the role of ecosystems in delivering these regulating ecosystem services, using the UK as our case study region. We identify some of the main co-benefits and trade-offs of ecosystem management within, and across, the regulating serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
126
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 62 publications
3
126
1
6
Order By: Relevance
“…Porto et al (2014) identified management strategies to minimize the trade-off between cost, fire risk and biodiversity objectives in cork oak forest landscapes with multiple landowners. Smith et al (2013) identified trade-offs of ecosystem management in the UK and found that optimal management is difficult to implement, in part because soil, water and air quality regulation are governed by different legislation. They also noted that the biggest conflict at a policy level may be caused by the fact that all regulating services, even if they are synergistic, may trade off against other ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porto et al (2014) identified management strategies to minimize the trade-off between cost, fire risk and biodiversity objectives in cork oak forest landscapes with multiple landowners. Smith et al (2013) identified trade-offs of ecosystem management in the UK and found that optimal management is difficult to implement, in part because soil, water and air quality regulation are governed by different legislation. They also noted that the biggest conflict at a policy level may be caused by the fact that all regulating services, even if they are synergistic, may trade off against other ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that the biggest conflict at a policy level may be caused by the fact that all regulating services, even if they are synergistic, may trade off against other ecosystem services. They conclude that ''an ecosystem services framework may improve the regulation of climate, and soil, water and air quality, even in the absence of economic valuation of the individual services'' (Smith et al 2013). The management of agriculture, forestry, water quality and biodiversity is regulated by different national and international legislation and conventions.…”
Section: Discussionmentioning
confidence: 99%
“…Had the increases in yield of the last 60-70 years not been achieved, almost three times more land would have been required to produce crops to sustain the present population; this is land that simply does not exist or that is unsuitable for cropping (5) . So intensification has been essential, but has resulted in many undesirable outcomes, including air, water and soil pollution (17) with agrochemicals and surplus nutrients, increased climate forcing (18) , resources depletion (19) , high fossil energy inputs (14) and habitat/biodiversity loss (11) . During the past century, then, while agricultural area expansion has continued, the emphasis for increasing food production has shifted towards intensification, i.e.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…A recent study mitigation potentials available from technical supply-side options [3], such as those considered in IPCC Fourth Assessment Report, were compared with the technical potential available from demand-side options, such as waste reduction and dietary change toward less GHG-intensive products (i.e., less meat and livestock products). This study found that the technical potential for a combination of demand-side options was between 1.5 and 15 Gt CO 2 -e/year by 2050, potentially much larger than the mitigation potential from supply-side measures in the AFOLU sector.…”
mentioning
confidence: 99%
“…This study found that the technical potential for a combination of demand-side options was between 1.5 and 15 Gt CO 2 -e/year by 2050, potentially much larger than the mitigation potential from supply-side measures in the AFOLU sector. Some of the mitigation potential arises from the potential for carbon sequestration (or use of bioenergy to displace fossil fuels) on the land freed by changes in demand, so even under scenarios of changed demand, carbon sequestration still has a potential role to play [3].…”
mentioning
confidence: 99%